C1-inhibitor attenuates neurobehavioral deficits and reduces contusion volume after controlled cortical impact brain injury in mice - Longhi, Luca; Perego, Carlo; Ortolano, Fabrizio; Zanier, Elisa R; Bianchi, Paolo; Stocchetti, Nino; McIntosh, Tracy K; De Simoni, Maria Grazia (Critical care medicine, 2009)
The aim of the study was to evaluate the effects of C1-inhibitor (C1-INH), an endogenous inhibitor of complement and kinin systems, on neurobehavioral and histological outcome following controlled cortical impact brain injury. Experimental prospective randomized study in mice. Experimental laboratory. Male C57Bl/6 mice (n = 81). Mice were subjected to controlled cortical impact brain injury followed by an intravenous bolus of either C1-INH (15 U either at 10 minutes or 1 hour postinjury) or saline (equal volume, 150 microl at 10 minutes postinjury). Sham-operated mice received identical surgery and saline injection without brain injury. Neurological motor function was evaluated weekly for 4 weeks using the Composite Neuroscore. Cognitive function was evaluated at 4 weeks postinjury using the Morris Water Maze. Histological outcome was performed by measuring the contusion volume at 1 week and 4 weeks postinjury. Brain-injured mice receiving C1-INH at 10 minutes postinjury showed attenuated motor deficits, cognitive dysfunction and reduced contusion volume compared to brain-injured mice receiving saline. Mice receiving C1-INH at 1 hour postinjury showed reduced motor deficits compared to brain-injured mice receiving saline, but no significantly different cognitive and histological outcome. Immunohistochemical analysis showed that 20 minutes after infusion, C1-INH was localised on endothelial cells and in brain tissue surrounding brain capillaries of the injured hemisphere. Our results show that post-traumatic administration of C1-INH attenuates neuro-behavioral deficits and histological damage associated with traumatic brain injury.